ETC Distance Learning Studies during COVID-19, a meta-analysis - Dreifuss-Serrano, Cristina (2022)
The recent increase in the amount of research on Distance Learning in Engineering, Technology, and Computing, produced by the adaptations in response to the sanitary emergency, makes it necessary to systematize, classify and analyze the current trends. This paper presents a meta-analysis of peer-reviewed papers written and published in the Iberoamerican region, regarding remote learning and distant teaching in ETC. Using PRISMA, we selected articles located in several academic repositories, which were classified in order to identify countries of origin, types of research (research, application, review), main keywords, and universities. The results were then analyzed to identify regional trends and possible lines of action to better ensure that the research efforts continue after the emergency.